Description of the parasitic fauna of a specimen of Didelphis albiventris at Rio Grande do Sul - Lignon, Julia Somavilla; Pinto, Diego Moscarelli; Monteiro, Silvia Gonzalez; Martins, Natália Soares; de Souza, Julia Victória; Meireles, Giulia Ribeiro; dos Santos, Tamires Silva; Pappen, Felipe Geraldo; Bruhn, Fábio Raphael (Brazilian Journal of Veterinary Medicine, 2024)
Didelphis albiventris is considered the most common marsupial in Rio Grande do Sul. With omnivorous and synanthropic habits, it can serve as a host to various parasites, playing an important role in maintaining their biological cycle. Despite being a widespread and abundant species, it has a relatively little-known parasitic fauna. Therefore, the aim of this study was to report the diversity of parasites in a fecal sample from D. albiventris in Rio Grande do Sul, Southern Brazil. Modified Centrifugal-flotation and Spontaneous sedimentation techniques were used, revealing a high taxonomic diversity of parasites. Eggs of Ancylostoma spp., Toxocara spp., and Anoplocephalidae were reported for the first time in the host in the southern region of the country, along with the first report of pseudoparasitism by Syphacia spp. and Monocystis spp. in this animal species. The presence of different parasites in the feces of D. albiventris is of utmost importance, primarily for public health, but also for understanding the biodiversity of parasites present in wildlife, which has been poorly studied until now. This allows the implementation of effective strategies for controlling, preventing and treating these diseases.